2013
DOI: 10.5114/kitp.2013.39737
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery Long-term follow-up in adult patients after Fontan operations

Abstract: Cel: Celem pracy była retrospektywna ocena częstości występowania powikłań oraz wpływu czasu pooperacyjnego na ich występowanie u dorosłych chorych po operacji Fontana w odległym okresie obserwacji. Materiał i metody: Do badania włączono kolejnych 48 chorych po operacji Fontana (26 M, 22 K) w wieku od 18 do 40 lat, średnio 23 ±5 lat. U wszystkich chorych wykonano badanie kliniczne, echokardiograficzne, laboratoryjne, EKG, wysiłkowy test spiroergometryczny oraz oceniono saturację krwi tętniczej. W zależności od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Our study shows that Fontan patients exhibit a decreased exercise capacity which is in line with previous studies concerning the adult patients with Fontan circulation [12,15,16]. In our group of Fontan patients maximum VO 2 was decreased.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study shows that Fontan patients exhibit a decreased exercise capacity which is in line with previous studies concerning the adult patients with Fontan circulation [12,15,16]. In our group of Fontan patients maximum VO 2 was decreased.…”
Section: Discussionsupporting
confidence: 81%
“…Those observations are in line with our study -we observed a trend towards a decrease of maximum HR and increase of HRR in Fontan patients according to postoperative time. A chronotropic incompetence can be related to an abnormal reflex control of heart rate or adrenergic dysfunction [2,16]. The HR plays an important role in controlling a CO in Fontan circulation during exercise [20].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, long-term antiplatelet therapy for prevention of thrombosis after Fontan operations is a reasonable consideration, even though thrombosis is a common feature (2)(3)(4). However, it is not known whether patients after Fontan operation respond to aspirin and whether aspirin resistance is prevalent in them (11)(12)(13).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The reported incidence of this life-threatening complication in FC patients ranges from 17% to 33% (1,2). The pro-thrombotic risk factors include previous thrombosis, type of arteriopulmonary connection, presence of thrombogenic foreign material, arrhythmias, slow venous flow, elevated central venous pressure, ventricular dysfunction, liver injury, effusion protein-losing enteropathy, and prolonged immobilization (3).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of low early mortality after Fontan procedure, patients are prone to several complications in long term, including arrhythmias, thrombo embolism, heart failure, pulmonary hypertension, cyanosis, liver dysfunction, protein-losing enteropathy, and restrictive lung diseases [5][6][7][8][9][10]. The occurrence of these complications and need for hospitalization influences the life expectancy and emotional, behavioral, and psychosocial condition of these patients.…”
Section: Introductionmentioning
confidence: 99%